Business model innovation to network collaboration and knowledge management practices in Thailand’s pharmaceutical industry entrepreneur - Kerdpitak, Chayanan; Suriyakul Na Ayudhya, Pattama; Insaad, Thitawan; Heuer, Kai (Kasetsart Journal of Social Sciences, 2023)
In a modern business environment, rapid development of network collaboration, knowledge practices, and technological capabilities are significant sources for the business model innovation (BMI). This study investigates the crucial impact of internal and external knowledge management capabilities and network collaboration on the BMI in pharmaceutical sector in Thailand. This study also evaluates the moderating impact of organizational risk-taking tolerance on BMI and suggests an alternative effective BMI. Population from 1,870 pharmaceutical firms in Thailand were empirically evaluated using confirmatory factor analysis, Structured Equation Modeling (SEM), and comparative analysis. The data were collected from 860 entrepreneurs from these 1,870 pharmaceutical firms. The sample size was determined based on the criterion of 20 times the observed variables. The outcomes from the SEM technique manifested that particularly internal knowledge management capabilities did not stimulate the model of business innovation of the pharmaceutical sector of Thailand. Furthermore, SEM results showed that external knowledge management capabilities can enhance the BMI of pharmaceutical firms, and network collaboration strengthens the BMI mainly with high organizational risk-taking tolerance.